2007
DOI: 10.1152/japplphysiol.01185.2006
|View full text |Cite
|
Sign up to set email alerts
|

Raising end-expiratory volume relieves air hunger in mechanically ventilated healthy adults

Abstract: Air hunger is an unpleasant urge to breathe and a distressing respiratory symptom of cardiopulmonary patients. An increase in tidal volume relieves air hunger, possibly by increasing pulmonary stretch receptor cycle amplitude. The purpose of this study was to determine whether increasing end-expiratory volume (EEV) also relieves air hunger. Six healthy volunteers (3 women, 31 +/- 4 yr old) were mechanically ventilated via a mouthpiece (12 breaths/min, constant end-tidal Pco(2)) at high minute ventilation (Ve; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…For example, retention of volume would cause greater lung stretch receptor activity, which is known to reduce air hunger. An increase in end-expiratory volume has been shown to relieve dyspnea in a similar model [17]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, retention of volume would cause greater lung stretch receptor activity, which is known to reduce air hunger. An increase in end-expiratory volume has been shown to relieve dyspnea in a similar model [17]. …”
Section: Discussionmentioning
confidence: 99%
“…The time traces of physiological variables and ratings were examined, and individual data points were excluded if any of the following a priori exceptions occurred during data point collection periods: 1) retention of air by the subject that raised end-expiratory volume by more than 50% of tidal volume, and consequently raised the subsequent end-inspiratory volumes (such volume increases reduce breathing discomfort [17]). 2) failure of the limiting bag to collapse on inspiration (at very low levels of stimulus drive), thus not fulfilling the criterion of limited ventilation.…”
Section: Methodsmentioning
confidence: 99%
“…Because high flow demands, and air hunger are the worst form of dyspnea it is important to understand which ventilator settings may relieve or worsen distress. Air hunger is reduced with increased levels of PEEP by increasing EELV ( Vovk and Binks, 2007 ) For example, spontaneous breathing at low levels of PEEP is associated with greater lung and diaphragm injury whereas spontaneous breathing at higher levels of PEEP is protective ( Yoshida et al, 2016 ; Morias et al, 2018 ). Physiologically, as lung volume increases mechanical receptors provide feedback to the brainstem, which depresses inspiratory effort and signals expiratory muscles for active exhalation if needed ( Road and Leevers, 1988 ; Road and Leevers, 1990 ; Torres et al, 1993 ).…”
Section: Myth #10—patients Must Be Spontaneously Breathing For Aprv T...mentioning
confidence: 99%
“…Sakurai et al ( 1998 ) similarly reported that lung expansion inhibited respiratory distress induced by airway occlusion in a dose-related manner and that bilateral vagotomy totally abolished this effect, presumably via loss of sensory feedback from PSRs. On the basis of these observations and the purported role of PSRs in the neuromodulation of breathlessness in humans (Manning et al, 1992 ; Flume et al, 1996 ; Vovk and Binks, 2007 ), it has been proposed that nebulized furosemide alleviates breathlessness by altering pulmonary vagal afferent activity from PSRs, presumably mimicking greater tidal volume (V T ) expansion (Nishino et al, 2000 ; Sudo et al, 2000 ; Nehashi et al, 2001 ; Moosavi et al, 2007 ; Nishino, 2009 ).…”
Section: Introductionmentioning
confidence: 97%